The Effect of Covid-19 Pandemic on The Financial Performance of Public Service Agencies: a Case Study at Jakarta Hospital - Masloman, Marlina; Nazikra R, Aditya; Alghiffari, Muhammad; Pambudi, Rizky S; Nasution, Nursanita (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study was conducted at The Jakarta hospital Hospital which is a Public Service Agency, aiming to determine the financial condition of the hospital before the covid-19 pandemic in 2018 and 2019 compared to after the covid–19 pandemic in 2020 and 2021. The type of research used is comparative descriptive research, and the data used in this study is a type of secondary data in the form of Financial Statements of Jakarta hospital, 2018 to 2021. The financial performance analysis used refers to the regulation of the Director General of Treasury No PER-24/PB/2018 on amendments to the regulation of the Director General of Treasury No PER-36/PB/2016 on guidelines for performance assessment of the Public Service Agency for Health Services and focuses on the financial aspects of the financial ratio subaspect of RS Jakarta. The results showed that the analysis of financial performance, financial aspects, sub-aspects of financial ratios before the Covid-19 pandemic compared to during the Covid-19 pandemic at Jakarta hospital, there was no decrease in non-tax revenues. Based on the ratio of PNBP income to operating costs or the ability of Jakarta hospital to finance hospital operations from its PNBP income, the Covid-19 pandemic condition has no effect on the ratio of PNBP income to operating costs.